MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE TGT TERHADAP PENINGKATAN MAHARAH ISTIMA' SISWA KELAS V SDIT LUQMAN PADANG - Fikri Alhamdi; Nur Atika Rima Ulinnuha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Thisiresearch is entitled “TheiEffect of TGT Type Cooperative Learning Modelion Maharah Istima' 5th Grade Students of SDIT Luqman Padang”. Theipurpose of this study was toiexamine how the effect of TGT type cooperative learning model on maharah istima' of 5th grade students at SDIT Luqman Padang. In this study, ia quantitative approach methodiwas used withia one group pretest-posttestiresearch design. The research objectiwas taken from the population of fifth grade students consisting of 137 students. Theisample was takenirandomly using random samplingitechnique with a total of 32 students. iData were collected through tests, and theiinstruments were tested for validity and reliability using theiSPSS version 26 application. The resultsiof the paired sample t-testishowed a significance level of 0.000, which indicated a significant influence between the applicationiof the TGT type cooperative learningimodel and maharah istima' of grade V students at SDIT Luqman Padang.